The Last Kiss Goodbye : A Novel - Robards, Karen (New York : Ballantine Books, 2013)
"When New York Times bestselling author Karen Robards brought her irresistible brand of hot passion and chilling suspense to the paranormal romance scene with The Last Victim, it was just the beginning. Now her all-new series cranks up the deadly danger and intense desire to the next level, as sexy serial killer hunter Charlotte Stone returns to action in her thrilling second adventure. THE LAST KISS GOODBYE Dr. Charlotte "Charlie" Stone has dedicated her career as a psychiatrist to exploring the darkest territory of all: the hearts and minds of serial killers. It's a job she's uniquely suited for, thanks to the secret talent that gives her an uncanny edge--Charlie can see dead people, whose tormented spirits cry out to her for the justice only she can provide. This blessing--or curse--gives Charlie the power to hunt down and catch madmen and murderers. It's also turned her love life upside down by drawing her into a hopelessly passionate relationship with the lingering ghost of charismatic bad boy Michael Garland. But there's little time for romance with her supernatural suitor when murder comes pounding at Charlie's door in the form of a terrified young woman fleeing a homicidal maniac. Saving her life places Charlie squarely in the cross-hairs of a sadistic predator nicknamed "the Gingerbread Man," notorious for manipulating his victims like pawns in a deadly chess game. And now the queen this psychopath's bent on capturing is Charlie. Refusal to play will only put more innocent lives in danger. Matching wits with this cunningly twisted opponent will require all of Charlie's training and expert skills. But even with her devilish "guardian angel"--not to mention her favorite flesh-and-blood Fed, Tony Bartoli--watching her beautiful back, the Gingerbread Man's horrifying grin might be the last thing Charlie ever sees. Praise for Karen Robards "One of the most popular voices in women's fiction."--Newsweek "Draw a line between two extremely popular genres, mysteries and romance novels, and in the middle you will find the bestselling Robards. She merges the two worlds like no one else, deftly interlacing plot and passion."--Albany Times Union Praise for The Last Victim "[An] exceptional storyteller. Leave it to Robards to deliver the start of a series that is distinctive and unforgettable!"--RT Book Reviews "Excellent. This story is going to haunt you."--Pittsburgh Post-Gazette "Thrilling. a fun and sexy read."--Booklist"--
"While on her evening run, serial killer expert Dr. Charlotte Stone comes across a bloodied and hysterical woman who raves to Charlie that she was forced to kill two others. Though unsure if this gut-wrenching story is true, Charlie gets her to a hospital. But then she remembers an almost identical story told to her by a prisoner incarcerated at Wallens Ridge. Drawing on her despised ability to communicate with the newly dead, Charlie discovers a vicious serial killer is on the loose. Dubbed the Ringmaster, this killer forces his kidnap victims to play sadistic, murderous games. VICAP Special Agents Tony Bartoli, Buzz Crane and Lena Kaminsky are investigating for the feds, with Charlie brought in to advise them. While Tony makes it clear that he would like to be more than friends with Charlie, she continues her love affair from Hell with dead man and convicted killer Michael Garland. In fact, it heats up as they track down this stone cold killer. At first, no one realizes that the Ringmaster is determined to involve Charlie in his evil games, but then it becomes terrifyingly clear that he's much closer than anyone realizes"--
Library Journal Prepub Alert
Adult.
Adult.
Keywords: Women forensic scientists -- Fiction; Women psychiatrists -- Fiction; Psychic ability -- Fiction; Serial killers -- Fiction; Criminal investigation -- Fiction; Mystery fiction; Romance suspense novels